1989
DOI: 10.1136/adc.64.10_spec_no.1374
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular output during postnatal circulatory adaptation in healthy infants born at full term.

Abstract: Left ventricular output was measured non-invasively at predefined time intervals from less than 15 minutes to 72 hours after birth in 16 infants who had been born at full term. The blood flow velocity in the ascending aorta was measured by a range gated Doppler technique and multiplied by the cross sectional diameter measured by cross sectional and M mode echocardiography. Left ventricular output remained high in the first two hours, 235-243 ml/min/kg, despite a 10% decrease in heart rate. The fall in heart ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
18
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 23 publications
5
18
1
Order By: Relevance
“…It is possible that the increase in LVO was missed in the first minutes as the first measurements were conducted between 3 and 7 min. However, Noori et al [85] have shown that increasing SV is important for CO during the first minutes after birth as it is later during transition [52]. …”
Section: Measurements For Evaluating Transitionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible that the increase in LVO was missed in the first minutes as the first measurements were conducted between 3 and 7 min. However, Noori et al [85] have shown that increasing SV is important for CO during the first minutes after birth as it is later during transition [52]. …”
Section: Measurements For Evaluating Transitionmentioning
confidence: 99%
“…After birth the increasing afterload will increase the likelihood of left-to-right shunt through the DA in the first days after birth. However, DA constriction will cause shunting through the DA to decrease [52]. Changes in SVR and the decrease in PVR resistance that occur during transition will cause blood pressure (BP) and flows in the pulmonary and systemic circulations to change.…”
Section: Hemodynamic Transitionmentioning
confidence: 99%
“…, 30 reflecting an adaption to the decreased demand on the left ventricle as the ductus arteriosus constricts and ductal left-to-right shunt decreases from 62 mL · min Ϫ1 · kg Ϫ1 at 1 to 2 hours of age to 14 mL · min Ϫ1 · kg Ϫ1 at 12 hours of age. 31,32 In human fetuses, the right heart dominance has been discussed controversially.…”
mentioning
confidence: 99%
“…During postnatal circulatory changes, 29 left cardiac output increases up to Ϸ240 mL · min Ϫ1 · kg Ϫ1 within the first 2 hours of birth because of increasing stroke volume. 30 Then left cardiac output falls to Ϸ190 mL · min Ϫ1 · kg…”
mentioning
confidence: 99%
“…In the present study, the left atrial to aortic root ratio and the inner diameter of the ductus arteriosus significantly increased in group 1 (mean age 1.8 hr after birth) compared with group 2 (mean age =13.0 hr after birth), thus the LV preload was suggested to be higher in group 1 than group 2. Several recent studies have shown that LV of human neonates have the ability to handle these increased preload imposed by PDA (Winberg et al 1989;Agata et al 1991), but the mechanism has not been clearly elucidated. As to the relationship between mVcfc and ESS, there was no significant difference between the 2 groups and the control in the slopes of the regression lines (Fig.…”
Section: Discussiqnmentioning
confidence: 99%